Business plan NGO: digital competences school for underprivileged youth in Colombia - Tinjacá, Olga Patricia Vargas (2017)
The following business plan presents a NGO that develops digital competence in Colombian underprivileged youth. Its objective is to increase the use of ICT for working and entrepreneur doing both: providing free lessons to youth and delivering digital outsourcing services to companies. To develop a suitable high-quality digital competence model and a sustainable business plan the inputs considered were: 1) The literature review: contains a PEST analysis to adjust the European DIGITCOMP model to the Colombian context, and the analysis of the Sesame Workshop business case as a success reference of an educative NGO. 2) The competitive analysis: evaluates the opportunities and threats of the outsourcing services industry where the NGO acquires financial resources and the weaknesses and strengths of the institution in comparison with others. 3) In-Depth interviews: examines the thoughts, perspectives, and knowledge of the owners of MSMEs regarding digital competence and the use of ICT. The outputs of the analysis are; the adapted version of DIGITCOMP presented in the product section of the marketing policy; the formulation of the development strategy for the NGO; and the policies for its implementation.